Cholecalciferol (VD3) Attenuates L-DOPA-Induced Dyskinesia in Parkinsonian Mice Via Modulation of Microglia and Oxido-Inflammatory Mechanisms. (Nigerian Journal of Physiological Sciences, 2022)
L-DOPA, the gold standard for managing Parkinson’s disease (PD) is fraught by motor fluctuations termed L-Dopa-Induced Dyskinesia (LID). LID has very few therapeutic options. Hence, the need for preclinical screening of new interventions. Cholecalciferol (VD3) treatment reportedly improves motor deficit in experimental Parkinsonism. Therefore, the novel anti-dyskinetic effect of VD3 and its underlying mechanisms in LID was investigated. Dyskinesia was induced by chronic L-DOPA administration in parkinsonian (6-OHDA- lesioned) mice. The experimental groups: Control, Dyskinesia, Dyskinesia/VD3, and Dyskinesia/Amantadine were challenged with L-DOPA to determine the abnormal involuntary movements (AIMs) score during 14 days of VD3 (30 mg/kg) or Amantadine (40 mg/kg) treatment. Behavioral Axial, Limb & Orolingual (ALO) AIMs were scored for 1 min at every 20 mins interval, over a duration of 100 mins on days 1,3,7,11 and 14. Using western blot, striatum was assessed for expression of dopamine metabolic enzymes: Tyrosine Hydroxylase (TH) and Monoamine Oxidase-B (MAO-B); CD11b, BAX, P47phox, and IL-1β. Cholecalciferol significantly attenuated AIMs only on days 11 & 14 with maximal reduction of 32.7%. Expression of TH and MAO-B was not altered in VD3 compared with dyskinetic mice. VD3 significantly inhibited oxidative stress (P47phox), apoptosis (BAX), inflammation (IL-1β) and microglial activation (CD11b). VD3 showed anti-dyskinetic effects behaviorally by attenuating abnormal involuntary movements, modulation of striatal oxidative stress, microglial responses, inflammation, and apoptotic signaling; without affecting dopamine metabolic enzymes. Its use in the management of dyskinesia is promising. More studies are required to further evaluate these findings.Keywords: Cholecalciferol; L-DOPA-Induced Dyskinesia; Parkinson’s Disease; Microglial; Oxidative stress; Inflammation